Regulatory framework of the international cooperation in education sphere (Russian experience) - Букалєрова, Людмила Олександрівна; Шагієва, Розаліна Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article is devoted to evaluation of the integration of Russia into the international educational area. The authors consider the agreements in the education sphere that have been ratified by Russian Federation. Also the authors note the ways of systematic and consistent convergence of the international legal institutions in relation to the legal regulation of the education system. Continuous complex process of integration of Russia into the international educational space, participation in the Bologna system require from the Russian Federation to take into account international legal standards for the regulation of education that should occur on an equal and mutually beneficial basis. The positive is that currently there is an intensive process of harmonization of the provisions of national law with the relevant norms of international law that proved by the adoption of the new Law on education, and a number of other legal acts.